The correlation between the conceptual metonymy and the process of generating proper names / A correlação entre a metonímia conceptual e o processo de geração dos nomes próprios (Revista de Estudos da Linguagem, 2020)
Abstract: Proper names can be considered lexical traces that identify a specific society and time as they enable us to better understand its modus vivendi, from its social-historical-cultural context. This study selects police operations proper names as subject study, and it is guided by the hypothesis that the generation of proper names configures as a cognitive process, which makes use of conceptual metonymy as a prominent contributor for several cognitive actions for naming. Thus, the focus is to demonstrate the conceptual metonymy role in the generation process of police operations proper names manifested by its typological features. The corpus for this analysis is composed of Brazilian Federal Police operations that were triggered in 2018 and can be obtained on its official website. The adopted methodology consists of mapping the proper names taxonomies according to Eccles’ three worlds (ECCLES, 1979) and metonymy typology, based on the proposal by Radden and Kovecses (2007); Blanco-Carrión, Barcelona and Pannain (2018); in addition to the theoretical foundations proposed by Lakoff and Johnson (1980), Lakoff (1987), Silva (1997) and Biderman (1998).Keywords: proper name; conceptual metonymy; cognitive linguistics.Resumo: Nomes próprios podem ser considerados marcas lexicais que identificam uma sociedade em determinada época, à medida que possibilitam a compreensão do modus vivendi dessa sociedade a partir do contexto sócio-histórico-cultural. Esta proposta elege nomes próprios de operações policiais para objeto de estudo e é guiada pela hipótese de que a geração desses nomes se configura como um processo cognitivo que faz uso de metonímias conceptuais, as quais oferecem uma contribuição de destaque na série de ações cognitivas para a nomeação. Assim, este trabalho tem como objetivo demonstrar o papel da metonímia conceptual no processo de geração dos nomes próprios das operações policiais manifestadas pelos traços tipológicos. O corpus para esta análise constitui-se de nomes de operações da Polícia Federal do Brasil desencadeadas no ano de 2018 e obtidos por meio de consulta ao site oficial dessa categoria de polícia. A metodologia adotada consiste no mapeamento das taxonomias dos nomes próprios de acordo com a natureza dos mundos (ECCLES, 1979) a que se reportam e no levantamento dos tipos de metonímias, baseada na proposta de Radden e Kovecses (2007) e de Blanco-Carrión, Barcelona, Pannain (2018), além da fundamentação teórica de Lakoff e Johnson (1980), Lakoff (1987), Silva (1997) e Biderman (1998).Palavras-chave: nomes próprios; metonímia conceptual; Linguística Cognitiva.